2011
DOI: 10.5830/cvja-2010-046
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and pattern of congenital heart diseases in a rural area of sub-Saharan Africa

Abstract: SummaryThe extent of congenital heart disease in Cameroon remains largely unknown. The aim of this study was to determine the occurrence and pattern of congenital heart diseases in the Cardiac Centre of St Elizabeth Catholic General Hospital, situated in a rural area of Cameroon.MethodsBetween November 2002 and November 2008, a population of 2 123 patients with suspected cardiac pathologies were consulted at St Elizabeth Catholic General Hospital referral cardiac centre. Of these patients, 292 subjects were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Many CHD cases in SSA are diagnosed at an advanced stage of their natural history when complications and contra-indications for corrective surgical interventions have already ensued [14,85]. A few hospitalbased studies with imaging capabilities have been conducted in SSA [9,14,[85][86][87]. A major study of 534 CHD patients at a cardiovascular referral center in Mozambique showed that complications were already present in 29% of cases at time of diagnosis.…”
Section: Congenital Heart Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Many CHD cases in SSA are diagnosed at an advanced stage of their natural history when complications and contra-indications for corrective surgical interventions have already ensued [14,85]. A few hospitalbased studies with imaging capabilities have been conducted in SSA [9,14,[85][86][87]. A major study of 534 CHD patients at a cardiovascular referral center in Mozambique showed that complications were already present in 29% of cases at time of diagnosis.…”
Section: Congenital Heart Diseasementioning
confidence: 99%
“…Among patients with an abnormality that needed surgical correction or palliation, only 41% of those could be operated with surgery contraindicated because of severe pulmonary hypertension, severe malnutrition, cardiomyopathy, neurological deficit, and HIV infection [14]. In the Cameroonian study, CHD patients requiring surgery were on the waiting list for more than three months before operation, and around 10% of patients died before their scheduled surgery, with surgical procedures completely paid for by not-for-profit organizations [85].…”
Section: Congenital Heart Diseasementioning
confidence: 99%
“…In patients with peripartum cardiomyopathy, prolonged corrected non-congenital QT interval and sinus tachycardia on baseline ECG were independent predictors of poor composite outcome which included death during follow-up [90]. Cardiomyopathies [58,61] Hypertensive heart disease [58,62,67] Coronary artery disease [58,59,61,64,69] Rheumatic heart disease [61,69] Congenital heart disease [96] Arrhythmogenic right ventricular cardiomyopathy [76,77] Hypertrophic cardiomyopathy [74,75] Brugada syndrome [78,79] Congenital Long QT syndrome (seen only in non-Black populations) [74,88,101] Ventricular non-compaction [84] Pulmonary embolism [62,91] Endomyocardial fibrosis [95] Pulmonary hypertension [61] Pericarditis (mainly tuberculous) [92] Aortic dissection/rupture [64] Endemic parasitic infections like trypanosomiasis & schistosomiasis [9,59,93] Sarcoidosis [102][103][104] Respiratory disease [58,62,64] Septicemia [58,66] HIV/AIDS [58,…”
Section: Reported Underlying Etiologies Of Sca/scd and Ventricular Armentioning
confidence: 99%
“…Endomyocardial fibrosis which is endemic in SSA has very poor prognosis with survival after diagnosis reported to be two years due to malignant arrhythmias, heart failure, and thromboembolism [95]. SCA/SCD due to congenital heart disease has been reported in SSA [96]. Short QT syndrome, catecholaminergic polymorphic ventricular tachycardia (CPVT), and other VTs forms have not been observed in the SSA literature.…”
Section: Reported Underlying Etiologies Of Sca/scd and Ventricular Armentioning
confidence: 99%
“…Congenital heart diseases (CHD) are of public health concern worldwide as they contribute signi icantly to childhood morbidity and mortality [1,2]. This is particularly so in developing countries, especially in sub-Saharan Africa, where non-communicable diseases in the paediatric age group are emerging major health and socioeconomic issues but facilities for early diagnosis and management are often lacking [2][3][4][5][6]. Congenital heart diseases (CHD) account for 8-12 / 1000 live births and approximately 30% to 40% of all individuals and also constitute appreciable inancial burden on the family and community [2,10].…”
Section: Introductionmentioning
confidence: 99%